ANALISIS PENGARUH STIMULI PEMASARAN TERHADAP PERSEPSI KONSUMEN DAN KEPUTUSAN KONSUMEN MEGGUNAKAN TV BERBAYAR MEREK INDOVISION DI KOTA PEKANBARU - Nasution, Indra Prasetya; Jushermi, Jushermi; Wijayanto, Gatot (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the influence of marketing stimuli on Consumer Perceptions and Consumer Decision Using Indovision’s Pay TV in Pekanbaru. In this study there were eight variables: Purchase Decision (Y2), Perception (Y1), Products (X1), price (X2), promotion (X3), People (X4), Physical Evidence (X5), Process (X6. The population of this research is all the people who use Indovision’s Pay TV in Pekanbaru with a sample of 98 respondents were selected using purposive sampling method. This data retrieval by giving questionnaires to respondents. Analysis of data in this study using path analysis with SPSS version 20. The results of this study indicate that the product variables and physical evidence of a significant effect on consumer peceptions using Indovision’s Pay TV while variable pricing, promotion, people, and processes does not have a significant effect . Then the variable product, promotion, and physical evidence of a significant effect on consumer 's decision to use pay TV of Indovision while variable pricing, people, and processes does not have a significant effect . And variable product ,price ,promotion ,people ,physical evidence, and the process has not been proven to have a stronger influence on consumer decisions using Indovision’s Pay TV after mediated by perception variables .Keywords : marketing stimuli , perception , purchasing decisions .